Vol. 141 : Smart Grids 2017: The Fifth International Youth Forum, October 9-13, 2017, Tomsk, Russia; [proceedings]; MATEC Web of Conferences - Kozyreva A. A. Alla Aleksandrovna; Zhdanova A. O. Alena Olegovna; Kuznetsov G. V. Geny Vladimirovich (2017, 2017)
Title screen